A New Class of Vitamin K Analogues Containing the Side Chain of Retinoic Acid Have Enhanced Activity for Inducing Neuronal Differentiation - Yoshihisa, Hirota; Taiki, Sato; Rina, Watanabe; Kazuki, Takeda; Sho, Sano; Satoshi, Asano; Yuki, Shibahashi; Yumi, Yusada; Yuta, Takagi; Yutaro, Yamashita; Wu, YuXin; Mikino, Arakawa; et al. (American Chemical Society, 2025)
Vitamin K, primarily known for its roles in coagulation and bone metabolism, has recently been implicated in neuroprotection and neuronal differentiation, particularly via its bioactive form, menaquinone-4 (MK-4). Here, we synthesized 12 vitamin K compounds with retinoic acidconjugated side chains and methyl ester modifications to enhance neuroactive properties. Among these, compound 7 demonstrated superior stability, robust transcriptional activation via steroid and xenobiotic receptor and retinoic acid receptor, and efficient induction of neuronal differentiation in mouse neural progenitor cells. Mechanistic analyzes revealed that Vitamin K activates metabotropic glutamate receptor 1 (mGluR1). Docking simulations confirmed its stronger mGluR1-binding affinity compared to MK-4. In vivo pharmacokinetics in C57BL/6 mice showed effective blood−brain barrier penetration, with compound 7 metabolizing into MK-4 over time. These findings establish compound 7 as a promising candidate for neurodegenerative disease therapies through its unique neuroactive mechanisms.